Isoflavone combined with exercise on bone mineral density in postmenopausal women: A systematic review and meta-analysis of randomized controlled trials. Issue 7 (July 2020) - Qiu, Shumin; Ma, Yue; Jiang, Chongmin
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: This meta-analysis of randomized control trials (RCTs) aimed to evaluate the effects of isoflavones supplementation combined with exercise training on bone mineral density (BMD) in postmenopausal women. Methods: Two reviewers did a complete search of two electronic database (Medline, PubMed) records up to January 31, 2019. Risk of bias was classified based on the Cochrane Collaboration tool. The pooled standard mean difference (SMD) combined with 95% confidence interval (CI) was used as the effect size of BMD values. Results: A total of four RCTs with 609 participants were included for meta-analysis. The BMD did not differ significantly between isoflavone supplementation combined with exercise training group and placebo group (sub-whole body: SMD = 0.00, 95% CI, –0.23 to 0.24; lumbar spine: SMD = 0.15, 95% CI, –0.30 to 0.60; total hip: SMD = 0.05, 95% CI, –0.18 to 0.298; femoral neck: SMD = 0.10, 95% CI, –0.23 to 0.43; trochanter: SMD = 0.09, 95% CI, –0.14 to 0.33; ward's triangle: SMD = –0.03, 95% CI, –0.24 to 0.30). In addition, combined intervention did not provide additive effects on BMD improvements compared with exercise or isoflavone supplementation alone. The trials included in this meta-analysis were small and some had methodological limitations. Conclusion: The present meta-analysis reveals that isoflavone supplements combined with exercise training do not significantly increase BMD in postmenopausal women. In addition, combined intervention does not provide additive effects on BMD improvements compared with exercise or isoflavone supplementation alone.